Classroom Management In EFL For Young Learners at SDIT Syahiral 'Ilmi : The Strategies And Challenges - Dafik Aditia Putra; Hilma Pami Putri; Hidayatul Haqqi (JURNAL JENDELA PENDIDIKAN, 2022)
This study aims to examine classroom management in EFL for young students, especially about strategies and challenges. This research uses qualitative methods with case study design and data collection techniques using semi-structured interviews and observation. The participants of this study were 2 English teachers who teach at SDIT Syahiral Ilmi and were selected using a purposive sampling technique where the participants involved were English teachers who taught as homeroom teachers. The findings of this study are that the teacher uses seating arrangements based on student qualifications and uses a rolling system, the teacher tries to maximize the lesson plan, the teacher corrects the students depending on the student's condition and based on the student's pronouncement, the teacher also uses storytelling strategies and by provoking students' curiosity, class rules read and agreed at the beginning of the semester. This study also found several challenges for teachers in classroom management including; there are some children who are hyper active in class, parents are dishonest to the teacher, discipline the class, make students focus, then there are some children who are inclusive.